Progenitor cells are responsible for formation of human prostate epithelium primary cultures - Drewa, T.; Wolski, Z.; Pokrywka, L.; Debski, R.; Styczynski, J. (Experimental Oncology, 2008)
To analyze cell viability and morphology of primary cell cultures from CD133 immunolabeled and sorted cells from epithelium of patients suffering from benign prostate hyperplasia (BPH). Methods: Cells obtained from 5 patients were divided in two fractions. First fraction (CD133+/CD133–) was cultivated in DMEM with 10% FBS. Second fraction was mixed with CD133 microbeads and immunomagnetically divided into CD133+ and CD133– fractions. These cells were cultivated and followed-up for 2 weeks. Cells were stained for Annexin V FITC/propidium iodide. Results: Seventy CD133+/CD133– cultures, thirty-one of CD133+ and thirty-one of CD133– cells were established. There were 5-fold and 3-fold increase of CD133+/CD133- and CD133+ cell number after 2 weeks, respectively. CD133+/CD133– and CD133+ monolayers displayed epithelial-like morphology and cytokeratine expression. CD133– cultures collapsed. Cell viability within CD133+ and CD133– populations was 90.1 ± 6.3% and 24.3 ± 6.2%, respectively. Apoptotic index was 9.0 ± 6.1% and 28.5 ± 23.8% within CD133+ and CD133– cultures, respectively. Conclusions: CD133 separated human primary epithelial cell cultures displayed differences in morphology, viability and apoptosis occurrence. Immunomagnetic sorting can be recommended in each in vitro experiments with primary cell cultures in order to provide more objective results. Цель: оценить жизнеспособность и морфологию клеток первичных клеточных культур, полученных из меченных по CD133
и полученных с помощью клеточной сортировки клеток эпителия пациентов с доброкачественной гиперплазией предстательной
железы (BPH). Методы: клетки, полученные от 5 пациентов, были разделены на 2 фракции. Первую фракцию
(CD133+/CD133–) выращивали в DMEM с 10% FBS али с CD133 магнитными гранулами и с помощью
магнита разделили клетки на CD133+- и CD133–-фракции. Далее клетки культивировали в течении 2 нед. Клетки
окрашивали аннексиномV FITC/пропидий йодидом. Результаты: получено 70 CD133+/CD133-
-культур клеток, 31 CD133+
и 31 CD133–. Через 2 нед культивирования отмечали 5-кратное и 3-кратное увеличение количества CD133+/CD133– и
CD133+ клеток соответственно. CD133+/CD133-
-и CD133+-клетки росли в монослое и имели морфологию эпителиальных
клеток, экспрессировали цитокератин. CD133–-клетки не выжили. Выживаемость клеток в популяциях CD133+ и CD133–
была 90,1 ± 6,3% и 24,3 ± 6,2% соответственно. Показатель апоптического индекса для культур CD133+ и CD133– был
9,0 ± 6,1% и 28,5 ± 23,8% соответственно. Выводы: показаны различия в морфологии, выживаемости клеток и частоте
апоптоза для эпителиальных клеток, разделенных в зависимости от экспрессии CD133. Сортировка клеток с помощью
иммуномагнитного разделения рекомендована для каждого in vitro эксперимента с использованием первичных клеточных
культур для получения более объективных результатов.